2015
DOI: 10.1111/jar.12186
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Control Trial of the 3Rs Health Knowledge Training Program for Persons with Intellectual Disabilities

Abstract: Health knowledge training is one step in promoting health self-advocacy and better health in persons with intellectual disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Strengthening health literacy could lead to more healthrelated participation [15,22,23]. However, it is important that information is accessible and understandable [24] [16] and the health-related knowledge is sufficient [23,25]. People with ID often have reduced health related knowledge and difficulty understanding information, so they depend on support from learning disability nurses or GP's [22][23][24][25].…”
Section: Promoting the Health Literacy Of People With Idmentioning
confidence: 99%
See 3 more Smart Citations
“…Strengthening health literacy could lead to more healthrelated participation [15,22,23]. However, it is important that information is accessible and understandable [24] [16] and the health-related knowledge is sufficient [23,25]. People with ID often have reduced health related knowledge and difficulty understanding information, so they depend on support from learning disability nurses or GP's [22][23][24][25].…”
Section: Promoting the Health Literacy Of People With Idmentioning
confidence: 99%
“…However, it is important that information is accessible and understandable [24] [16] and the health-related knowledge is sufficient [23,25]. People with ID often have reduced health related knowledge and difficulty understanding information, so they depend on support from learning disability nurses or GP's [22][23][24][25]. In order to provide this support, the communication of health professionals needs to be improved [15,22,24].…”
Section: Promoting the Health Literacy Of People With Idmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ex‐prisoners who are motivated and supported to engage with the healthcare system and self‐manage their own health‐related needs have improved physical and mental health compared with individuals who are unmotivated or poorly supported (Ludman et al ) and may be better equipped to address the challenges of community re‐entry. Recent research has shown that increasing healthcare knowledge, communication and self‐advocacy are feasible and effective in improving active healthcare engagement and self‐management for people with intellectual disability (McPherson et al ; Feldman et al ), forming an important component of inclusive, person‐centred service provision that promotes independence, provided it is matched to the individual's needs and ability (Howlett & Trollor ).…”
Section: Introductionmentioning
confidence: 99%